Pedagogical management as a concept of educational institutions development (Pedagogy of Higher and Secondary Education, 2012)
Malítska O. A. Pedagogical management as a concept of educational institutions development.The modern aspects of educational institutions’ modernization related to integration of national educational institutions into the unified European educational field were analyzed. The author systematized the main goals of pedagogical management and determined the functioning levels of management in educational field.
Keywords: pedagogical management; pedagogical production; conditions of effective management; effectiveness criteria